Simulation gaming : applications for sustainable cities and smart infrastructures : 48th International Simulation and Gaming Association Conference, ISAGA 2017, Delft, the Netherlands, July 10-14, 2017, Revised selected papers /: applications for sustainable cities and smart infrastructures : 48th International Simulation and Gaming Association Conference, ISAGA 2017, Delft, the Netherlands, July 10-14, 2017, Revised selected papers. (2018) - Unknown
No abstract available